Study of excipients influence on the cranberry oil releasing from the rectal suppository - I. M. Oliinyk; I. F. Bielenichev; M. I. Fedorovska; A. P. Lysianska (Zaporozhye State Medical University, 2019)
Cranberry oil is a sufficiently perspective compound for using in the semisolid rectal dosage forms because it possesses regenerating, antioxidative, anti-inflammatory actions together with practical toxicity absence. The aim of this work is the study of influence of the excipients, which are used in suppository manufacturing (delivery bases and surfactants) on the biopharmaceutical characteristics of the rectal dosage form with cranberry oil. Materials and methods. Concentration of surfactants in all rests was 2 % from the suppository mass, cranberry oil contain was 0.25 g in each suppository taking into account data of the advance investigations. Study was carried out according to plan of single-factor analysis of variance with repeated observations. Releasing of cranberry oil from the suppositories was chosen as a parameter of optimization for the first step of biopharmaceutical availability study. The study was carried out by equilibrium dialysis method by Kruvchinsky at the temperature 37.0 ± 0.5 ºС through the semipermeable film "Kuprofan". After 30 minutes the antioxidative activity was set on the model of non-fermentative initiation of the free radical oxygenation in all dialysates. Results. According to the presented data factor A (sort of base) and factor B (sort of surfactant) make significant influence on cranberry oil releasing from the suppositories (Fexp.>Ftabl). At the same time influence of the surfactants sort is slightly more significant than for the base. Also, interaction between these factors was statistically significant. On the base of obtained data, the range of influence of studied factors on the intensity of releasing of cranberry oil bioactive substances from suppository formulation was arranged: В > А > AxB. Conclusions. Variance analysis of results revealed that formulation with confectionary solid butter and emulsifier №1 provide optimal releasing of cranberry oil from the suppositories.